2010
DOI: 10.1021/cg1006583
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of Pyridine-N-oxide and Its Deuterated Analogues

Abstract: The aggregation of pyridine-N-oxide molecules in the solid state is very sensitive to small changes of the hydrogen/deuterium (H/D) exchange of the molecules and the thermal conditions during the crystallization process. The in situ crystallization of a partial deuterated pyridine-N-oxide allows the characterization of a low-temperature crystallographic phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 18 publications
(16 reference statements)
1
27
0
Order By: Relevance
“…The crystal structures of PNO [24] and PNO-D [11] were taken from the Cambridge Crystal Structure Database [27] (Release 2011). The molecular structure of the isolated molecules was optimized within the second-order Møller-Plesset perturbation theory [28] (MP2) using standard 6-311G(d,p) basis set.…”
Section: Analysis Of Crystal Structure Based On Quantum-chemical Calcmentioning
confidence: 99%
See 1 more Smart Citation
“…The crystal structures of PNO [24] and PNO-D [11] were taken from the Cambridge Crystal Structure Database [27] (Release 2011). The molecular structure of the isolated molecules was optimized within the second-order Møller-Plesset perturbation theory [28] (MP2) using standard 6-311G(d,p) basis set.…”
Section: Analysis Of Crystal Structure Based On Quantum-chemical Calcmentioning
confidence: 99%
“…The differences in chemical properties between H and D atoms are usually considered as a non-dominating parameter from the viewpoint of molecular and crystal structure. Under the same crystallization conditions, it was found that even partial deuteration of PNO led to the formation of a second polymorphic modification PNO-D [11] differing in the value of Z' and the character of the intermolecular C-H(D)···O contacts. [9] However, recently it was demonstrated that (H/D) exchange may lead to the formation of different polymorphic modifications.…”
Section: Introductionmentioning
confidence: 99%
“…The studies 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 Our own investigations of pyridine-N-oxide 48 have shown that partial deuteration influences the crystal packing of pyridine-N-oxide and leads to the formation of an isotopic lowtemperature crystallographic phase. Mono-deuterated pyridine-N-oxide crystallized from an under-cooled melt and is isostructural to pyridine-N-oxide in the tetragonal space group P4 1 2 1 2.…”
Section: Deuterium Isotope Effects On Hydrogen Bondsmentioning
confidence: 98%
“…Besides this intrinsic value, they can also be transformed into a useful tool for the synthesis of 'modified' peptides. [2] In continuation of our studies on 2(1H)-pyrazinones, [3] solid-state characterisation allowed to separate two conformational polymorphs of 5-chloro-3-phenyl-2(1H)-pyrazinone, the crystal growth of which was influenced by temperature. Form I crystallises from a methanol solution at room temperature in the monoclinic space group P21/c, whereas form II crystallises at low temperature in the centrosymmetric triclinic space group with two independent molecules in the asymmetric unit.…”
mentioning
confidence: 90%
“…Our own recent investigations of partially deutero-substituted pyridine-N-oxides yield two different polymorphs for a partial deuterated compound. Both the low-temperature and the high-temperature phases are stable and reversible [2,3] [1] …”
mentioning
confidence: 99%